BCG vaccine reactivation after mRNA immunization against COVID-19: case report - José Paulo Ribeiro Júnior; Maria do Carmo Araújo Palmeira Queiroz; Arnoud de Lucena Flor; Clause Willdys Medeiros Dantas (Revista Médica de Minas Gerais, 2023)
The Bacillus Calmette-Guérin (BCG) vaccine is a live attenuated pathogen vaccine used to prevent severe types of tuberculosis. A related immunological event is its scar reactivation. It is usually associated with Kawasaki disease and the use of other immunizers. In this report, we aim to describe the case of a 24-year-old woman with BCG vaccine scar reactivation after administering a Messenger RNA (mRNA) vaccine against COVID-19, BNT162b2. The pathophysiology involved in the scarring reactivation of the BCG vaccine is related to the chaperone proteins. There are still no cases reported in Brazil of BCG scar reactivation after mRNA vaccines. Nevertheless, we conclude that there is no evidence that such a reaction contraindicates a new dose of the vaccine.